Canadian Agility Movement Skill Assessment (CAMSA) in a Spanish Context: Evidences of Reliability and Validity. Issue 3 (3rd July 2022) - Menescardi, Cristina; Villarrasa-Sapiña, Israel; Lander, Natalie; Estevan, Isaac
ABSTRACT: The Canadian Agility and Movement Skill Assessment (CAMSA) is a circuit-based measure of motor competence. This study aimed to investigate the validity and reliability of CAMSA in Spanish children. A sample of 749 children participated voluntarily. Acceptable-to-good internal consistency (α = .54 and G-coefficient = .88) and moderate-to-excellent inter- (ICC: .83 to 1.00), intra-rater (ICC: .99 to 1.00) and test–retest reliability (ICC: .70 to .83) was found in convenience subsamples (n = 84 observers' reliability; n = 69 test-retest). Concurrent validity was moderate (CAMSA score with Körperkoordinationstest für Kinder : r = .45; n = 90). Confirmatory factor analysis supported the one-factor model (CFI = .95; RMSEA = .02; SRMR = .02). Boys had higher scores than girls and older-children had higher scores than younger-children. The CAMSA can be used as a valid and reliable instrument for assessing motor competence in Spanish children.